Common and Uncommon Variations of Pulmonary Venous Drainage in Patients Undergoing Thoracoscopic Lobectomy - Amore, Dario; Casazza, Dino; Imitazione, Pasquale; Curcio, Carlo (The Thoracic and Cardiovascular Surgeon, 2020)
Background Variations in pulmonary venous anatomy should not be undermined by thoracic surgeons during procedures which involve the pulmonary veins.Methods We have identified vascular anomalies in 25 of 346 patients undergoing video-assisted thoracoscopic surgery lobectomy at our Thoracic Surgery Unit, between December 2016 and November 2018.Results Some vascular anomalies described have not been reported in recent literature and include right V7 draining into the middle lobe pulmonary vein, accessory right V6 behind the bronchus intermedius, two V6 from the apical segment of left lower lobe, two V6 from the apical segment of right lower lobe, and one of them draining into the superior pulmonary vein.Conclusion Thoracic surgeons should be aware of this type of anomalies because failure in the preoperative or intraoperative identification of the pulmonary venous variations may lead to serious complications.
Keywords: thoracoscopy/VATS; lung cancer; pulmonary venous drainage